КАТАМНЕЗ ДЕТЕЙ ОПЕРИРОВАННЫХ ПО ПОВОДУ РЕТИНОПАТИИ НЕДОНОШЕННЫХ - Полякова, Галина Феликсовна; Гурина, Людмила Николаевна; Денисик, Наталья Ивановна; Бондарчук, Анастасия Николаевна (Медицина: теория и практика, 2020)